Persepsi Guru terhadap Integrasi Teknologi Informasi Komunikasi dalam Pembelajaran IPS Selama Daring - Sari, Indah; Adisel, Adisel (JOEAI (Journal of Education and Instruction), 2022)
This study aims to determine the teacher's perception of the integration of information and communication technology in online social studies learning at Karang Anyar Junior High School, Rupit District, North Musi Rawas Regency, South Sumatra Province. This study uses qualitative research methods that can be characterized and tend to use an inductive approach to analysis. with data collection techniques of observation, interviews and documentation. The research subjects were social studies teachers. The data analysis technique in this study used a qualitative descriptive data analysis interactive model from Milles and Michael Huberman which consisted of three concurrent activity lines, namely; data reduction, data presentation, and conclusion drawing. The research findings show that 1) teachers play an important role for students online. Teachers who are involved in online learning activities really help students to achieve a grade. 2) The implementation of the integration of ICT in this online period is by using power points, and also like voice recording so that students can understand what I explain when I teach online. In conclusion, the teacher's perception of the integration of Information and Communication Technology (ICT) in online social studies learning at SMPN Karang Anyar obtained information if the teacher has an important role for students in the online period. Teachers who are involved in the activities of the learning process really help students to achieve the expected competency targets Keywords: Information Communication Technology Integration, Teacher Perception, Online Social Studies Learning